2019
DOI: 10.1084/jem.20190414
|View full text |Cite
|
Sign up to set email alerts
|

Resident memory CD8 T cells persist for years in human small intestine

Abstract: Resident memory CD8 T (Trm) cells have been shown to provide effective protective responses in the small intestine (SI) in mice. A better understanding of the generation and persistence of SI CD8 Trm cells in humans may have implications for intestinal immune-mediated diseases and vaccine development. Analyzing normal and transplanted human SI, we demonstrated that the majority of SI CD8 T cells were bona fide CD8 Trm cells that survived for >1 yr in the graft. Intraepithelial and lamina propria CD8 Trm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
173
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(188 citation statements)
references
References 56 publications
15
173
0
Order By: Relevance
“…To note, intestinal Mfs do not express CCR7 (135,222,246), suggesting that they cannot migrate to mLNs to interact with naïve T cells in situ. Therefore, given that human intestinal T cells are almost entirely memory T cells (257)(258)(259), the biological significance of the ability of intestinal Mfs to regulate naïve CD4 + T cells as shown ex vivo is not clear.…”
Section: Function Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…To note, intestinal Mfs do not express CCR7 (135,222,246), suggesting that they cannot migrate to mLNs to interact with naïve T cells in situ. Therefore, given that human intestinal T cells are almost entirely memory T cells (257)(258)(259), the biological significance of the ability of intestinal Mfs to regulate naïve CD4 + T cells as shown ex vivo is not clear.…”
Section: Function Of Intestinal Mucosa Macrophagesmentioning
confidence: 99%
“…To note, Fenton et al recently showed that intestinal cDCs that highly express integrin αVβ8, such as cDC2, but not cDC1, might induce higher Treg polarization through TGF-β secretion (266). Nevertheless, given that there are few naïve CD4 + T cells in human intestinal mucosa (257)(258)(259), it is more relevant to study naïve CD4 + T cell polarization with cDCs from mLNs, as discussed below.…”
Section: Function Of "Total" Intestinal Mucosa Cdcsmentioning
confidence: 99%
“…Human SI Helios-Tregs, on the other hand, displayed turnover dynamics similar to noncirculating CD4 and CD8 Trm cells (19) (16), and persisted for >1 year in transplanted SI.…”
Section: Discussionmentioning
confidence: 99%
“…Only patients without clinical and histological signs of rejection were included. This approach provided a unique possibility to study the lifespan of tissue-resident cells directly because there is no recruitment of donor cells from the circulation (16)(17)(18). Because most donors and recipients express different HLA class I molecules, donor and recipient can be readily distinguished by flow cytometry (Fig.…”
Section: Helios+ and Helios-tregs Display Different Replacement Kinetmentioning
confidence: 99%
See 1 more Smart Citation